Au(III) Schiff base complexes as oxidoreductase inhibitors against carbapenem- and colistin-resistant Gram-negative bacteria via targeting redox active motifs - Xiuli Chen; Lin Lv; Jianqiang Xu; Jing Shi; Xi Chen; Guisha Zi; Yuxuan Wu; Shibo Sun; Yufan Pang; Qian Song; Ling Ma; Shuang Wei; et al. (Redox Biology, 2025)
Carbapenem- and colistin-resistant Gram-negative bacteria have become one of the most severe public health issues worldwide. The development of advanced antibacterial agents that can outpace microbial adaptation is imperative. The thioredoxin (Trx) and glutaredoxin (Grx) systems play important roles in maintaining redox homeostasis within Gram-negative bacterial cell membranes, with thioredoxin reductase (TrxR) and glutathione reductase (GR) being classical antibacterial targets. In this study, we found that Au(III) Schiff base complexes Au10 and Au17 exhibited potent activities against carbapenem- and colistin-resistant Gram-negative bacteria, as demonstrated in evaluations both in vitro and in vivo. Mechanistic studies revealed that Au10 and Au17 exert their antibacterial effects through multiple pathways: irreversibly inhibiting TrxR and GR activities via targeting redox-active motifs, impairing bacterial energy metabolism even at low concentrations, degrading deoxyribonucleic acid (DNA), causing reactive oxygen species (ROS) generation and intracellular redox imbalance. This study provides the first evidence that Au(III) Schiff base complexes possess strong activity against carbapenem- and colistin-resistant Gram-negative bacteria and can simultaneously inhibit the oxidoreductase in carbapenem- and colistin-resistant Gram-negative bacteria, establishing a new paradigm for antibacterial strategies and guiding future innovations in antibacterial therapy.